The angel of Indian Lake - Jones, Stephen Graham, 1972- (Jones, Stephen Graham, 1972- Indian Lake trilogy, 2024)
"It's been four years in prison since Jade Daniels last saw her hometown of Proofrock, Idaho, the day she took the fall, protecting her friend Letha and her family from incrimination. Since then, her reputation, and the town, have changed dramatically. There's a lot of unfinished business in Proofrock, from serial killer cultists to the rich trying to buy Western authenticity. But there's one aspect of Proofrock no one wants to confront... until Jade comes back to town. The curse of the Lake Witch is waiting, and now is the time for the final stand"--